Trends in generic prescribing and dispensing in Europe. Issue 4 (July 2008) - Simoens, Steven
Pressure to control pharmaceutical expenditure and price competition among pharmaceutical companies are fuelling the development of generic medicines markets in ambulatory care in Europe. The aim of this special report is to identify, interpret and discuss the main supply and demand trends affecting the European generic medicines market in ambulatory care. On the supply side, generic price-regulated systems and reference pricing systems are spreading across Europe. On the demand side, European countries have attempted to stimulate demand for generic medicines by focusing on physician prescribing, generic substitution by pharmacists and patient copayments. Finally, the development of biosimilars will probably become an important area of growth for the pharmaceutical industry over the next 5 years.